2013
DOI: 10.1007/s12017-013-8272-8
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Neuronal Loss in the Hippocampus of Aβ-Injected Rat: Autophagy, Mitophagy, and Mitochondrial Biogenesis Stand Against Apoptosis

Abstract: In the present study, we tried to answer the following questions: which kind of defense pathways are activated after Aβ insult? How defense systems react against noxious effects of Aβ and whether they are able to deal against apoptosis or not? So, we traced some molecular pathways including autophagy, mitophagy, and mitochondrial biogenesis before reaching to the endpoint of apoptosis. Besides, we measured the function of mitochondria after injection of Aβ (1-42) in CA1 area of hippocampus as a model of Alzhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 74 publications
5
23
0
Order By: Relevance
“…Accordingly, inhibition of Akt phosphorylation can explain decreased PGC-1a level in 3-MAadministrated rats with or without Ab injection. Since, as we reported previously (Shaerzadeh et al 2014), Ab significantly reduces PGC-1a in hippocampal neurons, it seems that deleterious effect of Ab and 3-MA on PGC-1a could be added to each other. As mentioned above, PGC1a binds to the cognate promoter of several genes that are involved in mitochondrial biogenesis like NRF-1, Tfam, and etc.…”
Section: Distanced Moved (Cm)supporting
confidence: 58%
See 2 more Smart Citations
“…Accordingly, inhibition of Akt phosphorylation can explain decreased PGC-1a level in 3-MAadministrated rats with or without Ab injection. Since, as we reported previously (Shaerzadeh et al 2014), Ab significantly reduces PGC-1a in hippocampal neurons, it seems that deleterious effect of Ab and 3-MA on PGC-1a could be added to each other. As mentioned above, PGC1a binds to the cognate promoter of several genes that are involved in mitochondrial biogenesis like NRF-1, Tfam, and etc.…”
Section: Distanced Moved (Cm)supporting
confidence: 58%
“…The end products of TCA cycle are reducing equivalents in the form of NADH and flavin adenine dinucleotide (FADH 2 ) as the first step of oxygen-dependent energy production. Our previous study indicated that activities of Aconitase and MDH enzymes severely decrease in the presence of Ab (Shaerzadeh et al 2014). In the present study, our data from biochemical tests further demonstrated that the activities of three enzymes of TCA cycle including Aconitase, a-KGDH, and MDH decreased when using 3-MA with or without Ab injection.…”
Section: Distanced Moved (Cm)mentioning
confidence: 95%
See 1 more Smart Citation
“…Our results also showed that mRNA levels and protein levels of mitochondrial biogenesis factors (PGC-1a, NRF 1, NRF 2, and Tfam) were reduced after 24-h incubation with Ab25-35. Similarly, intrahippocampal injection of Ab1-42 in rats resulted in decreases in PGC-1a, NRF 1, and Tfam (Shaerzadeh et al 2014). Taken together, these findings indicate that Ab suppresses mitochondrial biogenesis both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 61%
“…Impaired mitochondrial biogenesis contributes to mitochondrial dysfunction in AD (Sheng et al 2012). Moreover, mitochondrial biogenesis is severely affected and significantly decreases after injection of Ab in hippocampal CA1 area of rats (Shaerzadeh et al 2014). However, whether Ab suppresses mitochondrial biogenesis in primary hippocampal neurons remains unclear.…”
Section: Introductionmentioning
confidence: 99%